Dimensional accuracy of impression techniques for the endosteal implants (An in vivo study): Part II - Nadira A Hatim; Basim M Al-Mashaiky (University of Mosul, College of Dentistry, 2007)
Aims: To determine the most accurate impression techniques and materials to transfer the exact position of a single implant to stone die to construct the prosthesis for selected clinical cases. Materials and methods: Five clinical cases were selected with special criteria to construct implant (Frialit-2) prosthesis on a stone die with high accuracy according to the results of study. Four impression techniques were used (direct and indirect, each with one and two steps) using condensation, addition (heavy, medium and light consistencies) silicone impression materials. Ten impressions were taken for each patient to produce a total number of 50 stone casts. The direct and indirect measurements were performed by using digital vernier. Results: The significant differences between the impression techniques at the three axes of dimensions (p ≤0.05) were applied clinically to construct the fixed prosthesis for each patient. The results of this study showed that the high dimensional change of laboratory cast was related to indirect one step impression technique to transform the implant position from patient mouth to laboratory cast. Addition curing (medium consistency) silicone impression material produced the lowest accurate stone die. Conclusions: The results of this study showed that the direct two steps impression technique was the accurate impression technique for transformation of implant position from patient mouth to laboratory cast. Additional curing (light and heavy consistency) silicone impression material produced the most accurate stone die and gave a successful treatment to the patient.